Stuck on you: How dedication moderates the way constraints feel. (February 2015) - Knopp, Kayla C.; Rhoades, Galena K.; Stanley, Scott M.; Markman, Howard J.
Theorists agree that commitment has different components, but the interaction between two fundamental aspects of commitment—dedication (interpersonal commitment) and constraint (external pressures to stay together)—has not been examined to our knowledge. The effects of the interaction between dedication and constraint on several measures of discomfort were examined among adults in opposite-sex dating relationships ( N = 1, 294). In the context of lower dedication, greater material or perceived constraint was associated with more psychological distress, feelings of entrapment, and anxiety about abandonment. These results indicate that constraints feel subjectively different depending on interpersonal commitment to the relationship. Examining such interactions may help researchers better understand the role of constraints in the developmental course of romantic relationship commitment.